Pengaruh Pemadatan pada Campuran AC-WC dengan Bahan Filler Abu Kulit Kopi terhadap Nilai Volumetrik Marshall - Alfi Salmannur; Sofyan M. Saleh; Nadila Ernita (Universitas Iskandar Muda, 2025)
The quality of compaction of asphalt pavement layers, especially the wear layer (AC-WC) is very important to avoid damage. This study aims to analyze the effect of the number of compaction impacts on the Marshall characteristics of Asphalt Concrete Wearing Course (AC-WC) mixtures using coffee husk ash as a filler. AC-WC serves as an impermeable cover layer to protect the asphalt structure from water damage. The use of coffee skin ash as a filler material is expected to increase cost efficiency and utilize waste optimally. The research process began with physical material testing, sieve analysis, mix design, and the manufacture of 51 test samples. The number of compaction tumbles used were 2x35, 2x50, and 2x75. The results of the tests showed that increasing the number of compaction tumbles had a positive impact on the stability of the mixture, with a percent increase in stability values of 11% and 18.24%, respectively. The results also showed that the addition of 25% coffee husk ash had a positive impact on mix stability, with a percent increase in stability value of 11%. The flow, VIM, MQ and durability values of the 25% coffee husk ash mixture were also affected by the number of impacts. However, at 2x35 and 2x50 impacts, the flow, VIM, MQ and durability values did not meet the specifications of Bina Marga 2018 revision 2 . Thus, the optimal number of compaction impacts is very important to improve the durability and performance of AC-WC layers using coffee husk ash filler.